Peran Pendidikan Agama Kristen Gereja Berdasarkan Matius 28:19-20 dan Dampaknya Terhadap Pelayan Yang Maksimal di GKPS Siboro - Pasaribu, Lamtiur; Purba, Nurmaida Gressia (STT Injili Indonesia Medan, 2022)
Christian Religious Education in the local church has an important and significant role for the maximum of a service carried out by God's servants in the church. Based on this study of the text of Matthew 28:19-20, it is hoped that this research question can be answered. What is the role of the Christian education in the churchÂ is studied based on the process of word study and text exegesis. Through field research, authentic data was obtained regarding the implementation of Christian education in the Church based on verse studies and finding out its impact on maximum service. The purpose of this study is to describe the role of church Christian religious education based on Matthew 28:19-20. Furthermore, it proves that the implementation of the church's PAK based on Matthew 28:19-20 is significant in forming maximum servants and is still relevant to be applied in the church. The author also aims to explain the impact of the role of Christian Religious Education based on Matthew 28:19-20 on the maximum service at GKPS Siboro as the place for this research to be conducted.Keywords: Christian education, Matthew, church servant, maximum